ACADEMY OF THE MINISTRY OF INTERNAL AFFAIRS APPLICATION OF CROSSFIT EXERCISES IN THE PROCESS OF PHYSICAL TRAINING OF CADETS GIRLS - Mirzakulov Akrom Gafurjanovich (Proximus Journal Publishing, 2024)
Comprehensive physical fitness of Cadet Girls, health improvement, general endurance and fast-strength quality training, mastering the basics of running the competition in a combination way, developing special endurance, gaining competition experience.
Keywords: functional all-around; crossfit; physical education; physical culture